2014
DOI: 10.1016/j.actbio.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization- and solvent-induced phase separation in hydrophilic-rich dentin adhesive mimic

Abstract: Current dental resin undergoes phase separation into hydrophobic-rich and hydrophilic-rich phases during infiltration of the over-wet demineralized collagen matrix. Such phase separation undermines the integrity and durability of the bond at the composite/tooth interface. This study marks the first time that the polymerization kinetics of model hydrophilic-rich phase of dental adhesive has been determined. Samples were prepared by adding varying water content to neat resins made from 95 and 99wt% hydroxyethylm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 50 publications
1
49
1
1
Order By: Relevance
“…For the hydrophilic-rich phase, we suggested a possible polymerization mechanism involving PIPs and SIPs (Abedin et al 2014). Based on the proposed mechanism, microgels form following auto-acceleration, which are localized regions of a higher degree of conversion and/or cross-linking density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the hydrophilic-rich phase, we suggested a possible polymerization mechanism involving PIPs and SIPs (Abedin et al 2014). Based on the proposed mechanism, microgels form following auto-acceleration, which are localized regions of a higher degree of conversion and/or cross-linking density.…”
Section: Discussionmentioning
confidence: 99%
“…A fixed amount of liquid at 30 µL was placed on the horizontal face of the internal reflectance crystal. A transparent plastic cover slip was placed on the sample, and its edges were sealed using tape to prevent D 2 O evaporation during the collection of the data (Abedin et al 2014). In this study, D 2 O was used The rate of polymerization was evaluated from the first derivative of the time against conversion curve.…”
Section: Photopolymerization and Kinetics Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Lanza et al (4) identified HEMA in the culture medium in contact with MDPC-23 cells 24 h after the application of ASB and CSB to the occlusal sides of dentin discs. Studies have also demonstrated that HEMA is the main resin monomer capable of diffusing through dentin (23), since this monomer is responsible for promoting resin infiltration in deep demineralized dentin (9). It has been shown that this low-molecular-weight monomer is highly cytotoxic, causing pulp cell death mediated by oxidative stress and inhibiting cell phenotype expression related to healing (23).…”
Section: Properties Of Universal Adhesive Systemsmentioning
confidence: 99%
“…Next to the pulp chamber, the diameter and number of dentinal tubules per area increase, resulting in high permeability (5). This permeable substrate features a large quantity of dentinal fluid, which may interfere with the polymerization of resin materials enhancing the local presence of toxic unreacted free monomers (2,9). Therefore, since chemical composition of dental materials as well as the protocols of application to dentin play a central role in defining their mechanical behavior and compatibility with the pulp-dentin complex (2,5,10), the objective of this study was to evaluate the microtensile bond strength (µTBS) and transdentinal cytotoxicity of a universal adhesive system according to the hybridization strategies to dentin.…”
Section: Properties Of Universal Adhesive Systemsmentioning
confidence: 99%